2019
DOI: 10.1186/s13071-019-3738-7
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey of the prevalence and spatial distribution of ticks infesting cattle in different agro-ecological zones of Cameroon

Abstract: Background Ticks and tick-borne diseases are a major impediment to livestock production worldwide. Cattle trade and transnational transhumance create risks for the spread of ticks and tick-borne diseases and threaten cattle production in the absence of an effective tick control program. Few studies have been undertaken on cattle ticks in the Central African region; therefore, the need to assess the occurrence and the spatial distribution of tick vectors with the aim of establishing a baseline f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 53 publications
5
47
0
Order By: Relevance
“…These findings are in agreement with previous studies using the same techniques (Byaruhanga et al, ; Kiara et al, ; Njiiri et al, ). As previously mentioned, this difference could be explained by more frequent transmission of T. mutans in the field, by contrast with T. parva for which the main vector is apparently absent in Cameroon (Silatsa, Simo, et al, ), and for which transmission still needs to be demonstrated, although it seems likely based on the 23% T. parva seroprevalence such transmission may occur. Furthermore, unlike T. parva , T. mutans undergoes limited lymphocytic merogony.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…These findings are in agreement with previous studies using the same techniques (Byaruhanga et al, ; Kiara et al, ; Njiiri et al, ). As previously mentioned, this difference could be explained by more frequent transmission of T. mutans in the field, by contrast with T. parva for which the main vector is apparently absent in Cameroon (Silatsa, Simo, et al, ), and for which transmission still needs to be demonstrated, although it seems likely based on the 23% T. parva seroprevalence such transmission may occur. Furthermore, unlike T. parva , T. mutans undergoes limited lymphocytic merogony.…”
Section: Discussionmentioning
confidence: 94%
“…This could explain why most infections were detected in these areas. (Silatsa, Simo, et al, 2019b). It is, however, possible that other Rhipicephalus and Hyalomma species that are present in Cameroon for which the ability to transmit T. parva infection has been demonstrated experimentally could potentially evolve to become vectors in future (Norval et al, 1992;Theiler, 1909;Uilenberg, 1981 (Silatsa, Simo, et al, 2019b), the infected animals do not currently pose any risk of infection to naive cattle, although this situation could change in future, since certain AEZs, such as the Adamawa plateau, the western highlands and the coastal belt are climatically suitable for establishment of the major vector R. appendiculatus (Walker et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, the most economically important species, the invasive Asian cattle tick Rhipicephalus (Boophilus) microplus, is also the most notorious for rapid development of resistance to every new acaricidal product brought onto the market (Jonsson and Hope, 2007;Abbas et al, 2014). Acaricide-resistant R. microplus are widespread throughout tropical and sub-tropical Asia, Latin America and Australia (Abbas et al, 2014), and are rapidly spreading in Southern, Central and West Africa (Nyangiwe et al, 2018;Silatsa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%